Implantability, complications, and follow-up after transjugular intrahepatic portosystemic stent-shunt creation with the 6F self-expanding sinus-superFlex-Visual stent - Spira, Daniel (Iranian journal of radiology, 2016)
Background The transjugular intrahepatic portosystemic stent-shunt (TIPSS) builds a shortcut between the portal vein and a liver vein, and represents a sophisticated alternative to open surgery in the management of portal hypertension or its complications. Objectives To describe clinical experiences with a low-profile nitinol stent system in TIPSS creation, and to assess primary and long-term success. Patients and Methods Twenty-six patients (5 females, 21 males; mean age 54.6 years) were treated using a low-profile 6F self-expanding sinus-SuperFlex-Visual stent system. The indication for TIPSS creation was refractory bleeding in 9 of the 26 patients, refractory ascites in 18 patients, and acute thrombosis of the portal vein confluence in one patient. Portosystemic pressure gradients before and after TIPSS, periprocedural and long-term complications, and the time to orthotopic liver transplantation (OLT) or death were recorded. Results The portosystemic pressure gradient was significantly reduced, from 20.9 ± 6.3 mmHg before to 8.2 ± 2.3 mmHg after TIPSS creation (P < 0.001). Procedure-related complications included acute tract occlusion (n = 2), liver hematoma (n = 1), hepatic encephalopathy (n = 1), and cardiac failure (n = 1). Three of the 26 patients had late-onset TIPSS occlusion (at 12, 12, and 39 months after TIPSS creation). Three patients died within one week after the procedure due to their poor general condition (multiorgan failure, acute respiratory distress syndrome, necrotizing pancreatitis, and aspiration pneumonia). Another four patients succumbed to their underlying advanced liver disease within one year after TIPSS insertion. Seven patients underwent OLT at a mean time of 9.4 months after TIPSS creation. Conclusion The sinus-SuperFlex-Visual stent system can be safely deployed as a TIPSS device. The pressure gradient reduction was clinically sufficient to treat the patients’ symptoms, and periprocedural complications were due to the TIPSS procedure per se rather than to the particular stent system employed in this study.
Gesehen am 17.01.2019